Between climates of fear and blind optimism: the affective role of emotions for climate (in)action - Schlegel, Lena (Geographica Helvetica, 2022)
Emotions affect how humans relate to others and define their place in the world. They thus shape responses to socio-ecological problems like climate change. In spite of the overwhelming knowledge and concern about climate change, a lack of appropriate moral and political consequences prevails in most contemporary societies. Instead of trying to explain climate inaction as a result of (un)awareness, this paper introduces a new perspective by conceptualising climate inaction as an active social process animated by emotions. Drawing on an interdisciplinary and radically relational perspective, I grasp climate inaction as a product of more-than-human intra-action and explore the affective role of emotions within this production. To illustrate how emotions energise climate inaction, I sketch how fear, grief, and hope animate current climate responses.
Created from Fastlane, Scopus look-up